Managing people - Fournier, Camille (O'Reilly, 2018)
Part of your focus throughout this period of adjustment to management is to figure out your own management style. Many of you will be learning how to manage individuals while simultaneously being responsible for running a team. In the lesson, we'll talk about the challenges of dealing with the team as a whole, as well as how the technical side of your role might be changing, but it's important to start by considering the individuals. After all, your team is only as healthy as its individuals, and as the individual manager, you'll have a huge impact on each person.